2011
DOI: 10.1016/j.wombi.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiparous women's confidence to have a publicly-funded homebirth: A qualitative study

Abstract: Background: Hospital birth is commonly thought to be a safer option than homebirth, despite many studies showing similar rates of safety for low risk mothers and babies. Recently in Australia, demand has led to the introduction of a small number of publicly-funded homebirth programs. These offer homebirth to selected women who previously would not have considered this option. Women's confidence in having a homebirth through a publicly-funded homebirth program in Australia has not yet been explored. Aim: The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 33 publications
5
47
0
Order By: Relevance
“…This study confirms earlier work on women's perceptions of childbirth: Catling-Paul et al (2011) found women who choose homebirths were more likely to display confidence in the natural birth process and perceive less need for potential medical intervention [20].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study confirms earlier work on women's perceptions of childbirth: Catling-Paul et al (2011) found women who choose homebirths were more likely to display confidence in the natural birth process and perceive less need for potential medical intervention [20].…”
Section: Discussionsupporting
confidence: 89%
“…They are aware their choices will not be without an element of risk and employ practical and emotional coping strategies to manage these [21]. In discussions about place of birth, women prefer to focus on, and use language which reflects, concepts of safety rather than risk [20]. This study establishes women with high risk pregnancies also make decisions regarding place of birth with safety as their primary consideration.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…9,14 The home birth has been described as an extremely positive, significant and empowering experience. 9,12,15,16 Redundancy of pain relief, increased self-confidence, the participation of the whole family and achieving autonomy are all associated with home birth. 9,10,17 Information about the safety of home birth is contradictory.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They weighed the risks of home birth through information they had gathered and integrated with their experience of previous births, family support, and self-confidence. 13,14 Women who planned for a home birth tended to be more satisfied with the childbirth experience than those who planned to give birth in hospital, 15 they experienced less pain and required less pain relief. 16 No studies were found that addressed the reactions that woman face when choosing a home birth.…”
Section: Introductionmentioning
confidence: 99%